The Improving the Quality of Services In Junior High School 1 Malang - Leila Dwi Adzani Sukma; Rahmad Wijaya; Baroya Mila Shanty (Universitas Muhammadiyah Malang, 2021)
This study aims to determine which services need to be improved so that the number of new students increases. Using 5 research variables, namely tangible, reliability, responsiveness, assurance and empathy with the Quality Function Deployment (QFD) method approach which will produce a House of Quality matrix, a total of 12 service attributes need to be improved. After knowing the 12 service attributes that must be improved, the researcher conducted an interview with the Principal of JHS Muhammadiyah 1 Malang, so that eight technical responses were obtained, namely conducting discipline and character training for teachers, adding additional equipment, namely main textbooks, rulers, markers, erasers and attendance books. class, holding disciplinary training and human resource relations to staff, installing CCTV in the school area, namely in front of the teacher's room, each class and where students pass by (sports fields, bicycle / motorbike parking lots, and gazebos), adding gazebos and Wi-Fi in the school area then adding fiction story books in the library, adding school facilities such as toilets, improving school layouts so that the distance between classrooms and canteens, laboratories and libraries is close and maximizing social media such as Instagram, Facebook, and the school website in school promotion.